Reduced mother-child brain-to-brain synchrony during joint storytelling interaction interrupted by a media usage. Issue 7 (3rd October 2022) - Zivan, Michal; Gashri, Carmel; Habuba, Nir; Horowitz-Kraus, Tzipi
ABSTRACT: Parent–child synchrony is related to the quality of parent and child interactions and child development. One very emotionally and cognitively beneficial interaction in early childhood is Dialogic Reading (DR). Screen exposure was previously related to decreased parent-child interaction. Using a hyperscanning Electroencephalogram (EEG) method, the current study examined the neurobiological correlates for mother–child DR vs. mobile phone-interrupted DR in twenty-four white toddlers (24–42 months old, 8 girls) and their mothers. The DR-interrupted condition was related to decreased mother-child neural synchrony between the mother's language-related brain regions (left hemisphere) and the child's comprehension-related regions (right hemisphere) compared to the uninterrupted DR. This is the first neural evidence of the negative effect of parental smartphone use on parent-child interaction quality.